Lithium and strontium isotope hydrogeochemistry in Okayama and Tottori Prefectures, southwest Japan: implications for tracing slab-derived fluid - Manato Akishiba; Yoshiro Nishio (Progress in Earth and Planetary Science)
Abstract Dehydration of the Philippine Sea Plate during subduction beneath the forearc region of southwest Japan releases fluids into the crust, potentially producing Arima-type fluids, which are characterized by anomalous hydrogen and oxygen isotopic compositions (δD and δ 18O). Arima-type fluids have been identified in limited hot springs near active faults, such as the Arima and Takarazuka hot springs. The aim of our study is to understand why there have been limited reports of Arima-type fluids, despite the likelihood of their formation during slab dehydration. δ 7Li data can be used to identify Arima-type fluids in samples with Cl– concentrations below 3400 mg/L, whereas δD and δ 18O data have difficulty to detect them. In this study, we collected and analyzed samples from Okayama and Tottori Prefectures in southwest Japan, focusing on their chemical compositions and δ 7Li and 87Sr/86Sr values. We found that the δ 7Li and 87Sr/86Sr compositions of some of the water samples from Okayama Prefecture were similar to those of Arima-type fluids and that they are unlikely to be explained by other sources (e.g., local reactions with host rocks, residual hydrothermal/magmatic fluids, or seawater altered by rocks). Our results therefore suggest there may be a more extensive distribution of Arima-type fluids in the forearc region of southwest Japan than has been previously reported.